Swedish Archaeology in Perspective and the Possibility of Reflexivity - Åsa Berggren (Current Swedish Archaeology, 2001)
In exploring the possibilities of reflexivity in the Cultural Resource Management archaeology in Sweden, a comparison is made between the excavation at Çatalhöyük in Turkey and an excavation at Burlöv in Malmö, Sweden. The former, a large-scale research project that aims at implementing post-processual ideas, differs in many ways from the latter, which is part of a large-scale rescue project, Öresundsförbindelsen. There are also similarities, and in different ways reflexivity seems to be achieved in both cases.